2019
DOI: 10.3390/jcm8020193
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a 30-Day Slow-Paced Breathing Intervention Compared to Social Media Use on Subjective Sleep Quality and Cardiac Vagal Activity

Abstract: Breathing techniques are part of traditional relaxation methods; however, their influence on psychophysiological variables related to sleep is still unclear. Consequently, the aim of this paper was to investigate the influence of a 30-day slow-paced breathing intervention compared to social media use on subjective sleep quality and cardiac vagal activity (CVA, operationalized via high-frequency heart rate variability). Healthy participants (n = 64, 33 male, 31 female, M = 22.11, SD = 3.12) were randomly alloca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 50 publications
1
67
0
1
Order By: Relevance
“…Lehrer et al () have reported an increase in resting baroreflex gain (but not mean RR interval) after 10 weekly sessions of HRV biofeedback, while resting breathing frequency was not altered. Another study evaluating the influence of 30‐day SDB practice on cardiac vagal activity has found an increase in the morning and night HRV in the HF band (but not mean RR interval), also without alteration in the corresponding breathing frequencies (Laborde, Hosang, Mosley, & Dosseville, ). Only one study has reported a reduction in resting heart rate (suggesting an increase in cardiac vagal tone) after long‐term SDB paractice (Pal, Velkumary, & Madanmohan, ).…”
Section: Discussionmentioning
confidence: 99%
“…Lehrer et al () have reported an increase in resting baroreflex gain (but not mean RR interval) after 10 weekly sessions of HRV biofeedback, while resting breathing frequency was not altered. Another study evaluating the influence of 30‐day SDB practice on cardiac vagal activity has found an increase in the morning and night HRV in the HF band (but not mean RR interval), also without alteration in the corresponding breathing frequencies (Laborde, Hosang, Mosley, & Dosseville, ). Only one study has reported a reduction in resting heart rate (suggesting an increase in cardiac vagal tone) after long‐term SDB paractice (Pal, Velkumary, & Madanmohan, ).…”
Section: Discussionmentioning
confidence: 99%
“…Some methods that use slow paced breathing employ anti-hyperventilation instructions [2, 35]. However, the issue of hyperventilation is often overlooked and no anti-hyperventilation instructions are used [17, 33, 38]. Furthermore, paced breathing is currently widely implemented in many mobile applications [20, 21].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, research suggests that breathing at 0.1 Hz decreases pain, which makes it a promising complementary method for the treatment of chronic pain [14, 15, 16]. It can also improve sleep quality [17, 18] and decrease affective arousal [19], so it is a widely-used method of emotion regulation, that has recently been implemented in multiple mobile applications [20, 21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study, as well as several previous studies 10,11,17,18 , have studied the effects of only one intervention night on sleep. Previous studies using subjective assessment of sleep have shown that music listening 32,33 and slow breathing 34 can improve subjective sleep quality if practiced over several weeks. Moreover, it has been shown that music can have a cumulative effect on sleep quality, in that the effects of music increase over time 32,33,35,36 .…”
Section: Strengths and Limitationsmentioning
confidence: 99%